MANAGING MULTIPLE ACTIVITIES FOR SPECIFIC THEMES IN THE EFL CLASSROOM (PREK-GRADE 2) - Hughes M. Terry (Universidad Nacional de Colombia, 2002)
The theory of Multiple Intelligences by Howard Gardner is enlightening and extremely useful in the EFL (English as a Foreign Language) classroom. For starters it helps the teacher in understanding the individual differences found in the classroom and to comprehend how students go about learning. Multiple intelligences are not always taken into account even though they are very observable in children, since they are still so innocent and honest in their learning process. The purpose of this article is to discuss the importance of approaching the individuals encountered in our classroom, giving them the equal opportunity of learning another language and above all making our classes fun and resourceful so that these young learners are motivated for a lifetime.